Elective Mutism: School Intervention - Gómez Pulido, Ana (Pulso. Revista de educación, 2003)
Elective mutism can be classified either as a speech disorder or as a behavioural disorder. In this article, we will consider elective mutism as a fear of speaking, and thus a behavioural disorder. This perspective is supported by behaviourist, social learning, and psychodynamic theories. During childhood, individuals experience various fears, which can be adaptive if the child responds appropriately to the feared situation. However, if the fear persists and becomes a phobia, it is considered a behavioural disorder. There are several indicators that can assist in identifying elective mutism, and educational interventions must be tailored to these indicators. The token economy system is a valid intervention model for elective mutism that has been successfully used on multiple occasions.